2014
DOI: 10.1016/j.nima.2013.11.084
|View full text |Cite
|
Sign up to set email alerts
|

Collimation and decoupling of ECR source beams for brilliance optimization

Abstract: The four-dimensional transport of the transverse phase space of the extracted beam was calculated for the CAPRICE electron cyclotron resonance (ECR) ion source at GSI. The axial magnetic field adds an angular momentum to the extracted beam, resulting in a strongly x-y coupled beam. The report presents multi-particle tracking simulations, and the results illustrate that the beam brilliance can be improved by combination of multi-stage collimation with skew quadrupole decoupling. Quadrupole Collimation ChannelTh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Tracking simulations using three-dimensional magnetic field maps of finite solenoids confirmed that this omission is justified [21,22]. The four-dimensional rms emittance increase is proportional to the beam sizes on the stripper foil.…”
Section: Stripping Inside a Solenoidmentioning
confidence: 94%
“…Tracking simulations using three-dimensional magnetic field maps of finite solenoids confirmed that this omission is justified [21,22]. The four-dimensional rms emittance increase is proportional to the beam sizes on the stripper foil.…”
Section: Stripping Inside a Solenoidmentioning
confidence: 94%
“…[2][3][4] Interestingly, one of the recent trends in the beam physics community is to introduce coupling elements between two planes intentionally for sophisticated beam manipulations. [5][6][7][8][9] Several ideas have been proposed to generalize the original CS theory for the systematic beam dynamics description of such coupled systems with as much similarity as possible to the original CS theory. 6,10,11 In recent papers, 12,13 the dynamics of charged particles in general linear coupled lattices has been formulated in terms of a generalized CS theory, which extends the original CS theory to the fully coupled cases.…”
Section: Introductionmentioning
confidence: 99%
“…They used the solenoidal field of the electron source as inter-plane coupling element as well as a subsequent skew triplet. Application of this concept to ion beams is proposed in [4][5][6]. Exchange between the longitudinal and one transverse plane was considered and/or demonstrated in [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Application of this concept to ion beams is proposed in Refs. [5][6][7]. Exchange between the longitudinal and one transverse plane was considered and/or demonstrated in Refs.…”
mentioning
confidence: 99%